The metamorphosis and other stories - Kafka, Franz, 1883-1924.; Baker, Jason (New York : Barnes & Noble : Fine Creative Media, 2004)
Short stories presenting the author's view of the world as a hostile and dehumanized place.
A message from the emperor -- The metamorphosis -- The judgment -- The stoker: a fragment -- In the penal colony -- A country doctor -- An old leaf -- A hunger artist -- Josephine the singer, or the mouse people -- Before the law.
Includes bibliographical references (p. 189-191).
Keywords: Kafka, Franz, -- 1883-1924 -- Translations into English; Kafka, Franz, -- 1883-1924.; Translations